2017
DOI: 10.1155/2017/6835782
|View full text |Cite
|
Sign up to set email alerts
|

Switch to Aflibercept in the Treatment of Neovascular AMD: Long-Term Results

Abstract: Purpose To report the long-term clinical outcomes after switching from intravitreal bevacizumab or ranibizumab to aflibercept therapy in eyes with AMD. Methods Retrospective analysis of changes in BCVA, SD-OCT image, and frequency of injections after 1, 2, and 3 years of follow-up. Results 164 eyes were analyzed, 101 eyes switched from bevacizumab (group 1) and 63 from ranibizumab (group 2). One year after the switch, there was an overall nonsignificant mean decrease of 2 ETDRS letters in BCVA. Three years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…At 4 years, the CMT was maintained at 295 µm. Similarly, other switch studies demonstrated reduction in CMT [16][17][18][19]. In a retrospective switch study conducted by Cardoso et al, they evaluated patients who were switched from ranibizumab to aflibercept and the CMT decreased from baseline of 386.2 μm to 266.1 μm by year 3 [16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At 4 years, the CMT was maintained at 295 µm. Similarly, other switch studies demonstrated reduction in CMT [16][17][18][19]. In a retrospective switch study conducted by Cardoso et al, they evaluated patients who were switched from ranibizumab to aflibercept and the CMT decreased from baseline of 386.2 μm to 266.1 μm by year 3 [16].…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, other switch studies demonstrated reduction in CMT [16][17][18][19]. In a retrospective switch study conducted by Cardoso et al, they evaluated patients who were switched from ranibizumab to aflibercept and the CMT decreased from baseline of 386.2 μm to 266.1 μm by year 3 [16]. Wykoff et al published a 6-month prospective switch study to IAI with, CMT decreasing by 27.3 µm from time of switch [17].…”
Section: Discussionmentioning
confidence: 96%
“…Although VEGF family proteins activate three types of VEGF receptors (VEGFRs), the VEGFA/VEGFR2 axis elicits the most potent angiogenic activity and vascular permeability. Consequently, anti-VEGF drugs have shown great promise for the treatment of CNV (Angkawinitwong et al ., 2017; Neves et al ., 2017). Indeed, intravitreal injection of the VEGF antagonists ranibizumab (Lucentis) and aflibercept (Eylea) has been widely used to treat AMD (Mitchell et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Real-life data pertaining to the long-term stability under treatment with Aflibercept beyond two to three years are still scarce,3235 and few papers addressed predictive factors for long-term functional stability 3641. Clinical experience has taught that independent of the anti-VEGF drug in use, the PRN treatment strategy in RCTs and clinical practice has an inherent risk of under-treatment since lesion activity indicated by intraretinal fluid triggers re-treatment.…”
Section: Introductionmentioning
confidence: 99%